Environmental Status of a City Based on Heavy Metal Content of the Tree-Rings of Urban Trees: Case Study at Szeged, Hungary - Kiss, Tímea; Fekete, István; Tápai, Ibolya (Journal of Environmental Geography, 2019)
Urban vegetation, especially urban trees could act as ecological archives, as they reflect various elements of their environment. The main aim of the study is to evaluate the spatial and temporal variations of environmental conditions in the city of Szeged (Hungary) based on long-term monitoring of the heavy metal content of tree-rings (soft wood). In general, the living conditions of the urban trees (and other organisms as well) at Szeged was the worst in 2001/05, when the heavy metal pollution was the greatest, therefore the biomass production of the sampled trees decreased. Fortunately, the environmental conditions became better, only there are some points in the industrial area, where the heavy metal pollution of the environment is gradually increases. The temporal change in lead pollution (considerable decline in 2013/17) could be explained by the obligatory usage of lead-free petrol since 1999 and the diversion of through-traffic from the town (2011). The introduction of unleaded petrol had delayed favourable results, as the dust particles containing lead probably circulated in the air for a while before they were gradually become fixed in the soil or they were washed out from the town during heavy rains. The cadmium pollution also declined after the traffic diversion, as it is connected to the usage of brake-linings. Whilst the lead and cadmium content of the tree-rings decreased during the studied decades, the trees accumulated increasing amount of zinc throughout the studied periods, as this element could be up-taken from the ground-water, as the larger the canopy of a tree the denser and deeper its root system is.